2017
DOI: 10.1159/000484906
|View full text |Cite
|
Sign up to set email alerts
|

MEG3 Suppresses Human Pancreatic Neuroendocrine Tumor Cells Growth and Metastasis by Down-Regulation of Mir-183

Abstract: Background/Aims: Pancreatic neuroendocrine tumors (pNETs) are rare neoplasms which arise from pancreatic islet cells. Recently, lncRNA MEG3 has been reported as a tumor suppressor in variety cancers. This study aimed to reveal the functional effects of MEG3 on pNETs which has not been uncovered previously. Methods: The expression of MEG3, miR-183, and BRI3 in BON1 cells were altered by transfection with their specific vectors/shRNA, or mimic/inhibitor. Thereafter, cell viability, apoptosis, the protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…MEG3 is an imprinted gene within the DLK1-MEG3 locus located at human chromosome 14q32, which is the first lncRNA verified to act as a tumor suppressor and exert its anti-proliferative role through multiple signaling pathways [16,17,37,38]. Wei et al have revealed that MEG3 can inhibit proliferation and metastasis of gastric cancer via the p53 signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…MEG3 is an imprinted gene within the DLK1-MEG3 locus located at human chromosome 14q32, which is the first lncRNA verified to act as a tumor suppressor and exert its anti-proliferative role through multiple signaling pathways [16,17,37,38]. Wei et al have revealed that MEG3 can inhibit proliferation and metastasis of gastric cancer via the p53 signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data show that MEG3 is overexpressed in normal tissues [24] but downregulated in malignant tumors [10][11][12][13][14][15][16]. Low expression of MEG3 acts as an independent factor for predicting poor prognosis in cancer patients [12,15,25,26], and the downregulation of MEG3 is attributed to its promoter hypermethylation in cancer [27][28][29], and the negative modulation by DNMT1 in glioma [30].…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs), a group of non-coding transcripts that exceed 200 nucleotides in length, is associated with the proliferation, apoptosis and metastasis in a variety of cancers [7][8][9], of which lncRNA maternally expressed gene 3 (MEG3) has been reported to be downregulated in multiple malignancies such as nasopharyngeal carcinoma [10], tongue squamous cell carcinoma (TSCC) [11], hepatocellular carcinoma (HCC) [12], pituitary tumor [13], thyroid carcinoma [14], osteosarcoma [15], and epithelial ovarian carcinoma [16]. Loss of MEG3 or its polymorphisms is associated with clinal stage, distant metastasis, unfavorable survival in patients with thyroid and ovarian carcinomas [14,15], and contributes to cell hypoxia injury [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, a report regarded MEG3 as an explicit ceRNA in brain tumor [24]. Except of its competing role in brain tumor, MEG3 could also be an important ceRNA in other cancers and disorders [25,26]. Previous studies have demonstrated that miR-181a as a member of the miR-181family, which exerts as a tumor-promotor gene, is upregulated in many tumors, including chondrosarcoma and gastric cancer [27,28].…”
Section: Introductionmentioning
confidence: 99%